Factors Associated with Prescription Errors: Perspectives of Pharmacists in Community Pharmacies in Kigali, Rwanda - Nshimiyimana , Jean Pierre; Andegiorgish, Amanuel Kidane (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Prescription errors are a growing concern in global healthcare systems due to their impact on patient safety, treatment outcomes, and healthcare costs. This study aimed to identify factors associated with prescription errors from the perspective of pharmacists working in community pharmacies in Kigali, Rwanda. The significance of the study lies in its potential to inform strategies for minimizing medication errors, improving pharmaceutical care, and supporting evidence-based policy decisions in Rwanda’s healthcare system. A cross-sectional study design was employed using structured questionnaires administered to qualified pharmacists from randomly selected community pharmacies. Data were analyzed using STATA version 15 to determine the prevalence and contributing factors to prescription errors. The findings revealed several key issues, including illegible handwriting on prescriptions (63.64%), incomplete prescription details (66.23%), incorrect medication quantities (30.13%), and failure to check for patient allergies (48.05%). Statistically significant factors associated with prescription errors included unclear or conflicting information (AOR = 1.45; p < 0.001), lack of double-checking during dispensing (AOR = 1.48; p < 0.001), illegible prescriptions (AOR = 1.64; p < 0.001), limited access to patient information (AOR = 1.68; p < 0.001), and high workload (AOR = 2.15; p < 0.001). The study recommends the adoption of standardized and electronic prescription systems to eliminate handwriting-related errors, ensuring adequate staffing to manage workloads, and implementing continuing professional development programs to enhance pharmacists’ capacity in identifying and managing prescription errors. Collaboration among prescribers, pharmacists, and policymakers is critical in creating a safer medication dispensing environment in community pharmacies.